2011
DOI: 10.1039/c1cc14367k
|View full text |Cite
|
Sign up to set email alerts
|

Highly active iridium(i) complexes for the selective hydrogenation of carbon–carbon multiple bonds

Abstract: New iridium(I) complexes, bearing a bulky NHC/phosphine ligand combination, have been established as extremely efficient hydrogenation catalysts that can be used at low catalyst loadings, and are compatible with functional groups which are often sensitive to more routinely employed hydrogenation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…[9] Througho ur on-goings tudies, we have now established that non-aromatic unsaturated moieties containing as uitable donor group can also undergo selectiveC ÀHa ctivationa nd hydrogen-isotopee xchange (Scheme 1).…”
mentioning
confidence: 98%
“…[9] Througho ur on-goings tudies, we have now established that non-aromatic unsaturated moieties containing as uitable donor group can also undergo selectiveC ÀHa ctivationa nd hydrogen-isotopee xchange (Scheme 1).…”
mentioning
confidence: 98%
“…[12] In this regard, we have reported on the preparation and application of a series of new iridium complexes bearing a bulky Nheterocyclic carbene (NHC), 1,3-bis(2,4,6-trimethylphenyl)imidazol-2-ylidene (IMes), alongside an appreciably encumbered phosphine, and which have appreciable potential as highly active catalysts for HIE with deuterium. [13] Additionally, we have shown that these robust and practically accessible iridium species can be applied within the selective reduction of alkenes (and alkynes) [14] and in the Zselective dimerization of terminal alkynes. [15] Herein, we report the activity and selectivity spectrum of this class of iridium complex in the area of deuterium and, importantly, tritium labelling, as well as our initial investigations into the overall mechanism of the hydrogen isotope exchange process with these emerging catalyst species.…”
Section: Introductionmentioning
confidence: 99%
“…8 In relation to this, studies by Nolan et al have divulged that iridium species with the alternative specific combination of a bulky Nheterocyclic carbene (NHC) and a pyridine ligand represent appreciably robust complexes that are active within both alkene hydrogenation 9 and transfer hydrogenation protocols. 10 In view of these findings, and based on the knowledge that judicious and careful manipulation of the ligands supporting the iridium centre is critical for success within hydrogen isotope exchange processes, we turned our attention to the application of the general class of Ir(NHC)(py) complexes Our initial investigations involved the preparation of catalysts 3a-c 9,10 via the modified preparative procedure shown in Table 1.…”
Section: Scheme 1 Hydrogen Isotope Exchange Processmentioning
confidence: 99%